Overlord : D-Day and the battle for Normandy - Hastings, Max. (New York : Simon and Schuster, 1984)
Describes the military effort by which the Allies regained the continent of Europe in World War II.
"Much the greatest thing we have ever attempted" -- Preparations: commanders; airmen; invaders; defenders -- To the far shore: the overture; the American beaches; the British beaches; Inland -- The British before Caen: closing the lines; Villers-Bocage; EPSOM -- The Americans before Cherbourg: the bocage; the battle for Cherbourg -- The German army: stemming the tide: Soldiers; weapons -- The battlefield: from the beachhead to the front; casualties -- Crisis of confidence: the fall of Caen; GOODWOOD -- The breakout: COBRA; the limits of air power -- The open flank -- The road to Falaise -- The gap -- Appendices: Glossary ; Chronology of the Normandy Campaign ; Allied Order of Battle ; German land forces encountered by the Allies in Normandy.
Maps on lining papers.
Includes bibliographical references (pages 350-353) and index.
Keywords: 1939-1945; Operation Overlord; World War, 1939-1945 -- Campaigns -- France -- Normandy; Normandy (France) -- History; History